BIG DATA SUPPORT FOR PROJECT MANAGEMENT IN THE CONDITIONS OF WAR: THE EXPERIENCE OF UKRAINE (International Journal of Innovative Technologies in Economy, 2023)
The article contains a review of the unique Ukrainian experience of launched and implemented projects in the conditions of a global risk, i. e. the war. It is highlighted that the large-scale invasion of the Russian Federation on the Ukrainian territory caused global threats and risks for public and business organizations and the Ukrainian society as a whole. The emphasis is made on top innovative projects of Ukraine launched and implemented (or being rapidly developed) due to the intensive use of digitalized processes. The authors presented a review of global reforms in the areas of strategic importance for Ukraine: development of road infrastructures in Ukraine, modernization of heath protection sector, reduction of Ukraine’s dependence on energy imports (especially on Russia), development of digitalized processes, improvement of the education quality and bringing the domestic education system in conformity with European standards. These reforms involved the development of megaprojects that could be successfully implemented several years before the beginning of the war and continue to be extensively used in daily activities of Ukrainian citizens. The issue of big data implementation as a useful ground for the successful accomplishment of projects in the conditions of war and the future postwar period is elaborated on.